Teacher education for inclusion - the premises for implementing a new initial teacher training programme - Marin, Elena (Special Education, 2016)
This paper attempts to highlight and examine the Romanian perspective regarding inclusive education by presenting some statistical data and the steps that have been made in order to make the switch from a school system lead by the segregation principle to a school system based on inclusive principles. Moreover, the attention focuses on schools` key actors, the teacher, more specifically on the initial teachers training programmes available in Romania. The starting point when it come to the initial teacher training programmes is based on the assumption that there is an acute need for training when it comes to the implementation of an inclusive educational system in Romania. Using a qualitative approach, we aimed at presenting specialists’ opinion on priority issues in policy development regarding the teacher training in the field of inclusive education, focusing on the premises for implementing a training system that is mandatory for every teacher in the inclusive education and on the aspects that relate to the rethinking of the teacher’s training process at a national level.
Keywords: inclusive education; initial teacher training; teachers competences; diversity; Romania